Ժամանակակից ջերմոցային տնտեսությունների արտադրանքի ինքնարժեքի մեջ փոփոխուն ծախսերի վերլուծությունը - Արտակ Անանյան (ՀՀ ԳԱԱ հրատ.)
В статье рассматривается необходимость и важность составления бизнес-планов тепличных хозяйств в условиях современных рыночных отношений. По результатам исследовательской работы автором проводится анализ основных переменных затрат в себестоимости продукции современных тепличных хозяйств. Рассматривается изменение динамики перемен-ных затрат тепличных хозяйств с производственными площадями 10560, 40550 и 100000 кв/м. В статье при анализе любого вида переменных затрат принимаются во внимание возможные способы экономии последних, а также их влияние на финансовую стабильность и повышение эффективности деятельности в рамках проблемы.The article first justifies the need and importance for designing business plans by Armenian commercial greenhouses at the current stage of development of the market economy. Then, based on the research results, the author analyzes the main variable costs in per unit cost structure of modern commercial greenhouses. The author provides the dynamics of variable costs when the area of a commercial greenhouse is 10,560, 40,550 and 100,000 square meters. While analyzing each type of variable costs, the article provides possible methods of reducing the discussed costs and their impact on financial stability of companies within the context of increasing the effectiveness of performance.
Keywords: Հասարակական գիտություններ; Տնտեսագիտություն; Ֆինանսներ